Environmental history recorded in aeolian deposits under stone pavements, Mojave Desert, USA. Issue 1 (January 2016) - Dietze, Michael; Dietze, Elisabeth; Lomax, Johanna; Fuchs, Markus; Kleber, Arno; Wells, Stephen G.
Abstract : Reconstructing the evolution of arid landscapes is challenged by limited availability of appropriate environmental archives. A widespread surface feature — stone pavement — traps aeolian fines and forms a special accretionary archive. Seven stone pavement-covered sections on basalt flows in the eastern Mojave Desert are condensed into a composite section, comprising five sedimentological units supported by an OSL-based chronology. Three of the units are of accretionary nature and each is covered by a stone pavement. They were deposited > 50.9–36.6 ka, < 36.6–14.2 ka and < 14.2 ka, and they are intimately coupled with the history of nearby Lake Mojave, which advances the current understanding of regional aeolian activity. End-member modeling analysis of grain-size distributions yielded seven sediment transport regimes. The accretionary system operates in two modes: A) episodic formation of a stone pavement by lateral processes once a vesicular horizon has formed on a barren surface; and B) accretion of dust and eventual burial of the clast layer. These findings improve current concepts about stone pavement evolution and their environmental proxy function in arid landscapes. Stone pavement-covered accretionary deposits are a new key archive that allows quantifying the relative importance of dust accretion, slope processes, soil formation and vegetation cover.